A computational work on turbulent flow and heat transfer in a channel fitted with inclined baffles - Saim, Rachid; Bouchenafa, Rachid; Benzenine, Hamidou; Öztop, Hakan Fehmi; Al-Salem, Khaled; Abboudi, Said (Springer, 2013)
Numerical studies of momentum and heat transfer characteristics have been investigated of a steady incompressible turbulent flow of air through channel. The channel has inclined baffles which are arranged on the walls in a periodically staggered way. The governing equations, namely, continuity, Navier-Stokes and energy, based on k-omega turbulence model to describe the turbulence phenomenon are solved using the finite volume method and the SIMPLE algorithm. Calculations are performed for a Reynolds number between 12,000 and 38,000. The axial velocity profiles, the velocity fields, the local and average coefficient of friction and the Nusselt number distribution were obtained for all the geometry considered and for different sections selected, upstream, downstream and between the two inclined baffles. Simulation results which were obtained by the use of baffles are validated by an experimental study. Good agreement is observed between numerical and experimental results data in the literature.
Keywords: Rectangular Channel; Enhancement